Examining shortened versions of the Social Responsiveness Scale for use in autism spectrum disorder prediction and as a quantitative trait measure: Results from a validation study of 3–5 year old children. Issue 4 (5th October 2022) - Lyall, Kristen; Rando, Juliette; Toroni, Bridget; Ezeh, Tobechukwu; Constantino, John N.; Croen, Lisa A.; Garvin, Brigid; Piselli, Kate; Connell, James; Kaat, Aaron J.; Newschaffer, Craig J.; ,
Abstract: Background: The Social Responsiveness Scale (SRS) is a 65‐item measure yielding a continuous score capturing autism‐related traits. Scores based on SRS item subsets have been analytically examined but administration of shortened versions has not been evaluated prospectively. Objective: The goal of this study was to compare psychometric properties of two shortened versions of the SRS to the full 65‐item SRS, in young children from both a clinical and general population setting. Methods: Study participants (aged 3–5 years) were drawn from the AJ Drexel Autism Institute clinic ( n = 154) and Kaiser Permanente Northern California ( n = 201) and block randomized to receive either the 16‐item short SRS, a newly developed computer adaptive testing‐SRS, or the published full‐length SRS. Total scores across the three SRS administration methods were scaled to facilitate comparisons. Scores were plotted to assess distributional properties, while Receiver Operating Characteristic analysis was used to estimate Area Under the Curve (AUC) and address predictive ability. Results: Overall, distributional properties of the three administration methods were highly comparable, with shortened measures demonstrating similar ability to capture the range of the distribution and case non‐case separation as the full SRS. In addition, AUC values were high (0.91–0.97) and comparable across the administration methods, though there was evidence of difference in predictive ability across measures for females (AUC for full SRS = 0.99 vs. 0.84 for short). Within individual comparisons of short versus full scores (available only for participants at the general population site) suggested underestimation of actual full SRS scores with the CAT‐SRS. Conclusions: Our findings broadly support the construct validity and performance of shortened SRS versions examined here, though the full measure may be needed to more accurately assess traits consistent with ASD diagnosis in females. This work suggests opportunities for collection of ASD‐related phenotype in settings where participant burden or feasibility considerations may have otherwise prohibited such measurement.